The application of randomised controlled trials for urban policy evaluation in smart cities: a systematic literature review - Pereira, Mauro (2022)
Pereira, M., Neves, F. T., & Neto, M. D. C. (2022). The application of randomised controlled trials for urban policy evaluation in smart cities: a systematic literature review. In Livro de Resumos da Conferência do Projeto de Investigação Científica “Fatores de Transformação Urbana (DRIVIT-UP)” em conjunto com I Conferência sobre Ciência de Dados para Ciências Sociais e VI Conferência de Planeamento Regional e Urbano. [Abstract book from the Conference of the Scientific Research Project “Drivers of urban transformation (DRIVIT-UP)” a joitly event with I Conference on Data Science for the Social Sciences And VI Conference on Regional and Urban Planning] (pp. 38-40). UA Editora. https://doi.org/10.48528/pkzd-wz70